EHRA White Paper: knowledge gaps in arrhythmia management—status 2019. Issue 7 (18th March 2019) - Goette, Andreas; Auricchio, Angelo; Boriani, Giuseppe; Braunschweig, Frieder; Terradellas, Josep Brugada; Burri, Haran; Camm, A John; Crijns, Harry; Dagres, Nikolaos; Deharo, Jean-Claude; Dobrev, Dobromir; Hatala, Robert; et al.
Abstract: Clinicians accept that there are many unknowns when we make diagnostic and therapeutic decisions. Acceptance of uncertainty is essential for the pursuit of the profession: bedside decisions must often be made on the basis of incomplete evidence. Over the years, physicians sometimes even do not realize anymore which the fundamental gaps in our knowledge are. As clinical scientists, however, we have to halt and consider what we do not know yet, and how we can move forward addressing those unknowns. The European Heart Rhythm Association (EHRA) believes that scanning the field of arrhythmia / cardiac electrophysiology to identify knowledge gaps which are not yet the subject of organized research, should be undertaken on a regular basis. Such a review (White Paper) should concentrate on research which is feasible, realistic, and clinically relevant, and should not deal with futuristic aspirations. It fits with the EHRA mission that these White Papers should be shared on a global basis in order to foster collaborative and needed research which will ultimately lead to better care for our patients. The present EHRA White Paper summarizes knowledge gaps in the management of atrial fibrillation, ventricular tachycardia/sudden death and heart failure.